Alternate ways to preserve strains with silica gel - R. L. Metzenberg (Fungal Genetics Reports, 1994)
The method for storing Neurospora strains described by D. D. Perkins (Can. J. Microbiol 8:591-594, 1962; Neurospora Newsl. 24:16-17, 1977) and elaborated in a collection of articles in Neurospora Newsl. 26 has made it possible to keep large collections with much less effort than would be required with the older lyophil method. In Perkins' method, conidia are suspended in sterilized non-fat milk, and the suspension is pipetted onto chilled sterile silica gel. For non-conidiating strains, mycelia are mulled or otherwise fragmented in milk to make the suspension. However, even this greatly improved method requires a non-trivial amount of manipulation when large numbers of strains are to be preserved, especially for non-conidiating strains. Preparing each stock consumes a pipet and at least two test tubes: one for growth of the strain, and one for preservation. Both tubes need to be labelled, which adds to the effort and to the chance of error. The following method requires no pipetting. The stock is preserved in the tube in which it was grown.